Mathematics 2 - DJABI, Abdelmoumene (Setif1 University Ferhat ABBAS , Faculty of Economics , Business and management Sciences , Department of basic education, 2025)
This work includes a comprehensive set of summaries, exercises, and solutions designed to enhance the understanding of core concepts in linear algebra. Key topics covered include matrices, determinants, matrix inverse, systems of linear equations, eigenvalues, eigenvectors, and diagonalization. Each chapter includes practice exercises designed to help students apply theoretical knowledge, accompanied by solutions for self-assessment, allowing students to track their progress and solidify their understanding
Summaries and Exercises
: تتضمن هذه الدراسة مجموعة شاملة من الملخصات، والتمارين، والحلول المصممة لتعزيز فهم المفاهيم الأساسية في الجبر الخطي. تشمل المواضيع الرئيسية المصفوفات، المحددات، معكوس المصفوفة، أنظمة المعادلات الخطية، القيم الذاتية، المتجهات الذاتية، والتقطيع القطري. يحتوي كل فصل على تمارين تطبيقية تهدف إلى مساعدة الطلاب في تطبيق المعرفة النظرية، مصحوبةً بحلول للتقييم الذاتي، مما يسمح للطلاب بتتبع تقدمهم وتعزيز فهمهم
Keywords: Déterminant; Valeurs propres; Inverse d'une matrice; Algèbre linéaire; Matrice; Systèmes d'équations linéaires.; المحدد، القيم الذاتية، مقلوب المصفوفة، الجبر الخطي، المصفوفة، جمل معادلات خطية; Determinant; Eigenvalues; Inverse of matrix; Linear Algebra; Matrix; System of linear equations